2007
DOI: 10.1109/iscc.2007.4381589
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Approach for Supporting Streaming Media: Design, Implementation and Experiments

Abstract: Future Internet traffic will be dominated by ondemand streaming media flows, such as IPTV, 3D/HD video, gaming, virtual reality, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…In 11, the authors made a test where they demonstrated that the future Internet traffic will be dominated by video streaming and on‐demand multimedia applications such as IPTV, stereoscopic/HD video, games, virtual reality, etc. Future network architectures need to offer new features such as scalability, QoS, TCP traffic high support, and so on.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In 11, the authors made a test where they demonstrated that the future Internet traffic will be dominated by video streaming and on‐demand multimedia applications such as IPTV, stereoscopic/HD video, games, virtual reality, etc. Future network architectures need to offer new features such as scalability, QoS, TCP traffic high support, and so on.…”
Section: Related Workmentioning
confidence: 99%
“…Currently, any network architecture needs to offer new multimedia services, including stereoscopic IPTV. As indicated in 11, in order to achieve a scalable IP packet switching, we have to minimize ‘stopping’ of the serial bit streams. It will reduce the buffer size, jitter and packet loss.…”
Section: Network Performance Without Codingmentioning
confidence: 99%
“…UNDERLYING PRINCIPLES AND TECHNOLOGIES As the context of this work is a network performing PF of packets, this section briefly introduces this technology and its deployment options. An extensive and detailed description of PF is outside the scope of this paper and is available in the literature [6,7,16,18,26].…”
Section: Introductionmentioning
confidence: 99%
“…Future navigation systems like the European Galileo and the Chinese BeiDou will only improve the availability of a global time reference. Alternatively, several solutions for distributing the synchronisation reference directly through the network can be adopted; see for instance [16,17], and, specifically for TDP, [18].Although the availability of global time empowers global coordination, it does not mean that synchronisation needed for PF comes for free, as it requires the ability, for both end systems and routers, to send packets 'at the correct time' to properly respect the schedule. Specially considering the end systems, this may be a challenge because of the so called 'latency', which can be informally defined as the difference between the time when a packet should be received (sent), and the time when it is actually received (sent).…”
mentioning
confidence: 99%
See 1 more Smart Citation